Conselho Consultivo da Área de Proteção Ambiental (APA) de Cairuçu: um olhar sobre a gestão participativa - Souza, Paula Callegario de (2020)
This work aimed to analyze opportunities and challenges of taking part in protected areas management councils in order to promote sustainable development, in the light of the experience of the Cairuçu Environmental Protection Area - APA’s Management Council, also called CONAPA Cairuçu. To assess properly this experience of participatory management, we have analyzed availabledata such as literature review, legislation and documents produced by CONAPA, as well as gathering info through observation as participant and semi-stwctured interviews, that were systematized and based on the Grounded Theory (Flick, 2009). The Cairuçu Environmental Protection Area was created in the early 1 980s and covers half of the municipality of Paraty, state of Rio de Janeiro. The purpose of this protected area is to ensure the protection of the Atlantic Forest and the local caiçaras communities integrated into this ecosystem (BRASIL, 1983). However, the territory covered by the APA is the target of disputes that mixes multiple interests, from large enterprises and private interests and the way of life of traditional communities that live in the area. In recent years, we have identified a change in institutional policy (ordinances of the management body of the Conservation Unit encouraging community participation) and the maturation of social movements, leading them to occupy institutional spaces of participation, bringing to light the objective of creating conservation units and qualified demands and actions aimed at the collective good and the environment. In this sense, this research brings a look at CONAPA Cairuçu, a participatory space in which we had the opportunity to participate as an advisor, in addition to having used the methods of participant observation and interviews with key informants. Among the main results we canhighlight a few numbers of decisions and policies obtained through social participation in the Management Council of the Cairuçu Environmental Protection Area, such as: Revision of the Management Plan; Tekoa Itaxi Mirim Prior Consultation Protocol; Term of Authorization for Sustainable Use - TAUS. We realize that, Participatory management at the Cairuçu APA provided greater anchorage of the conservation unit.